2009
DOI: 10.1016/j.mimet.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

The mycolyltransferase 85A, a putative drug target of Mycobacterium tuberculosis: Development of a novel assay and quantification of glycolipid-status of the mycobacterial cell wall

Abstract: CitationThe mycolyltransferase 85A, a putative drug target of 55 56 57 58 59 60 61 62 63 64 65 66 67 68 The enzymes of the Antigen 85 complex (Ag85A, B, and C) possess mycolyltransferase activity and catalyze the synthesis of the most abundant glycolipid of the mycobacterial cell wall, the cord factor. The cord factor (trehalose 6,6'-dimycolate, TDM) is essential for the integrity of the mycobacterial cell wall and pathogenesis of the bacillus. Thus, TDM biosynthesis is regarded as a potential dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
(19 reference statements)
1
21
0
Order By: Relevance
“…In parallel, Elamin et al (54) developed a colorimetric assay with FbpA using the natural TMM substrate to form TDM and trehalose, the latter being quantified by a series of coupled reactions (conversion into glucose which is oxidized in gluconic acid and hydrogen peroxide ultimately used to form the oxidized (brown) form of o-Dianisidine). Later, an ESI-MS (ElectroSpray Ionisation-Mass Spectrometry) assay was reported that uses a labelfree approach and permits a complete dissection of the kinetic steps of the mycoloyl transfer from TMM to trehalose, TMM or other derivatives (55).…”
Section: Catalytic Activity Of Mycoloyltransferasesmentioning
confidence: 99%
“…In parallel, Elamin et al (54) developed a colorimetric assay with FbpA using the natural TMM substrate to form TDM and trehalose, the latter being quantified by a series of coupled reactions (conversion into glucose which is oxidized in gluconic acid and hydrogen peroxide ultimately used to form the oxidized (brown) form of o-Dianisidine). Later, an ESI-MS (ElectroSpray Ionisation-Mass Spectrometry) assay was reported that uses a labelfree approach and permits a complete dissection of the kinetic steps of the mycoloyl transfer from TMM to trehalose, TMM or other derivatives (55).…”
Section: Catalytic Activity Of Mycoloyltransferasesmentioning
confidence: 99%
“…4). High-throughput screening assays were reported for FadD32 (Galandrin et al 2013) and the antigens 85 Elamin et al 2009;Sanki et al 2009;Favrot et al 2013). The latter assays led to the identification of a number of inhibitors of antigens 85, one of them, known as ebselen, also shows activity against Mtb in culture (MIC of 20 mg/mL).…”
Section: Drugs Targeting Mycolic Acid Biosynthesis and Exportmentioning
confidence: 99%
“…Phosphonate inhibitors of Ag85C have been synthesized, with the most active molecules possessing a MIC range of 188 to 319 g/ml against M. avium in broth culture, with optical density (OD) as readout (20). Recently, modified enzymatic assays for high-throughput screening of Ag85 proteins have been reported (12,19). However, Ag85 antagonists, which inhibit division of pathogenic M. tuberculosis, and their mechanisms of action have not yet been reported.…”
mentioning
confidence: 99%